Is antimicrobial stewardship cost-effective? A narrative review of the evidence. (November 2017) - Naylor, N.R.; Zhu, N.; Hulscher, M.; Holmes, A.; Ahmad, R.; Robotham, J.V.
Abstract: Aims: This narrative review aimed to collate recent evidence on the cost-effectiveness and cost–benefit of antimicrobial stewardship (AMS) programmes, to address the question 'is AMS cost-effective?', while providing resources and guidance for future research in this area. Sources: PubMed was searched for studies assessing the cost-effectiveness, cost–utility or cost–benefit of AMS interventions in humans, published from January 2000 to March 2017, with no setting inclusion/exclusion criteria specified. Reference lists of retrieved reviews were searched for additional articles. Content: Recent evidence on the cost-effectiveness and cost–benefit of AMS is described, studies suggest persuasive and structural AMS interventions may provide health economic benefits to the hospital setting. However, overall, cost-effectiveness evidence for AMS is severely limited, especially for the community setting. Recommendations for future research in this area are therefore provided, including discussion of appropriate health economic methodological choice. Implications: Health systems have a finite and decreasing resource, decision makers currently do not have necessary evidence to assess whether AMS programmes provide sufficient benefits. Although the evidence-base of the cost-effectiveness of AMS is increasing, it remains inadequate for investment decision-making. Robust health economics research needs to be completed to enhance the generalizability and usability of cost-effectiveness results.